A new residue method for the determination of flonicamid in agricultural and environmental samples using enzyme immunoassay systems. Issue 42 (12th April 2016) - Liu, Zhenjiang; Ren, Kewei; Li, Ming; Wang, Jiagao; Sun, Jianfan; Du, Daolin
Abstract : An indirect competitive enzyme-linked immunosorbent assay (ELISA) for flonicamid was developed based on a polyclonal antibody. Abstract : An indirect competitive enzyme-linked immunosorbent assay (ELISA) for flonicamid was developed based on a polyclonal antibody. 4-Trifluoronicotinic acid (TFNA) was used as flonicamid hapten and conjugated to bovine serum albumin (BSA) to produce an immunogen and ovalbumin (OVA) to produce a coating antigen. Polyclonal antibodies against flonicamid were successfully produced by immunizing New Zealand white rabbits. Under the optimal conditions, the 50% inhibitory concentration (IC50 value) of standard curves was 7.89 mg L −1 and the limit of detection (IC10 ) was 0.063 mg L −1 . There was almost no cross-reactivity of the antibody with three structurally related metabolites, indicating that the antibody had high specificity. The recoveries from spiked water, soil, tomato and apples were in the range of 82.4–113.4% with relative standard deviations of 2.9–10.3%. Moreover, the ELISA for spiked samples showed reliability and high correlation with gas chromatography. These results suggest that the proposed ELISA method has potential application for screening flonicamid in agricultural and environmental samples.